Alcohol Use is Not Directly Related to the Perceived Control of Depressive Symptoms in Patients with Depressive Symptoms - Skule, Cecilie; Dallavara, Hilde; Ulleberg, Pål; Berge, Torkil; Egeland, Jens; Landro, Nils I. (Frontiers in Psychiatry, 2014)
Treatment seeking patients (N= 233) were recruited as they started a course of relapse prevention and coping with depression. The mean Beck Depression Inventory (BDI-II) score was 26 points, indicating a moderate degree of depression. The sample was recruited from different outpatient clinics and screened for alcohol-related problems with The Alcohol Use Disorders Identification Test (AUDIT). More than 40% of the total sample had a score on AUDIT >8 indicating an alcohol problem. A specific instrument, Perceived Uncontrollability of Depression (UNCONTROL), was used to measure the persons’ perceived control of depressive symptoms. Alcohol problems were not found to be significantly associated with the perceived control of ongoing depressive symptoms and did not moderate the relationship between depressive symptoms and the perceived control of depressive symptoms. The results question the assumption that alcohol use is related to coping with depressive symptoms in patients with alcohol abuse and depression.